Development of traditional medicinal plants on Peatland conditions in Central Kalimantan - Jaya, Herry Palangka; Ludang, Yetrie; Mangkoedihardjo, Sarwoko (Journal of Phytology, 2022)
Most of the total peatland area in Kalimantan Island and particularly in Central Kalimantan Province is suitable for agricultural development. This condition provides a great opportunity for the development of peatlands for the cultivation of traditional medicinal plants. The local society in their daily lives could not be separated from the inherent elements of tradition even though the development of science and technology is currently very fast. One of the traditional elements that are inherent at this time is the use of medicinal plants as a solution in treating various diseases. The research was conducted in Palangka Raya City, Central Kalimantan Province by conducting interviews to determine the type of selected medicinal plants and carrying out experiments for examining their ability to absorb carbon dioxide and to grow in peatland conditions. The results of the study of four types of traditional medicinal plants show that there is great potential for two types of plants, namely Semar Bags and Karamunting, whose implementation fulfills biodiversity in an agricultural land ecosystem.